`Time to take the stage`: a contextual study of a high performance coach - Consterdine, A.; Newton, J.; Piggin, S. (Sports Coaching Review, 2013)
Fayyaz Ahmed, generally known as Fuzz, is the UK Athletics National Event Coach for High Jump, and the coach of Olympic bronze medallist Robbie Grabarz. Fuzz trained at The Royal Academy of Dramatic Art (RADA) in London and implements RADA principles into his coaching. The aim of this study was to explore the complexities and shades of self, social interaction and micro-behaviour through an illumination of a case study using this elite level coach. An interpretive phenomenological analysis using Goffman (1959) as a theoretical lense, explored Fuzz's delivery through semi-structured interviews and observational field notes. We used a multifaceted approach in data interpretation, incorporating a deductive method alongside continual analysis and theme generation. The main findings, drawn from Goffman's concepts of performance, manner and front, highlight the intricacies of the coach-athlete relationship and the continual development of the coaching persona.